Communication strategies used by Parkinson's nurse specialists during healthcare interactions: A qualitative descriptive study. (14th March 2022) - Pitts, Emilie; Wylie, Karen; Loftus, Andrea M.; Cocks, Naomi
Abstract: Aim: To explore the range and use of communication strategies by Parkinson's nurse specialists, and describe key communication strategies, to support health professionals in their healthcare interactions with people with Parkinson's. Design: A qualitative descriptive study. Methods: Due to the COVID‐19 pandemic, the study took place in an online setting. Online semi‐structured interviews were conducted with eight Australian Parkinson's nurse specialists and one UK Parkinson's nurse between August and October of 2020. Interviews explored healthcare communication, specifically (1) ways Parkinson's nurse specialists support communication during healthcare interactions, (2) factors influencing the use of communication strategies, and (3) how the nurses learned to communicate effectively with people with Parkinson's disease. Reflexive thematic analysis was used to analyse the data. Results: Parkinson's nurse specialists described the importance of establishing strong therapeutic relationships, the key role of the communication partner, adapting communication to reduce cognitive load, ensuring two‐way understanding, and enabling expressive communication for people with Parkinson's. Knowing the person and family, knowing the disease and understanding the symptoms appeared to influence the choice of communication strategies in healthcare interactions. Learning through others, learning through experience and learning through education and research were considered important parts of becoming a skilled healthcare communicator when working with people with Parkinson's. Conclusion: Knowledge and use of effective communication strategies to support people with Parkinson's is crucial for all health professionals working with this population, in order to reduce the occurrence of poor healthcare outcomes. A deep understanding of how Parkinson's disease affects communication and experience in implementing communication strategies were reported as contributing to the success of Parkinson's nurses in communicating with their patients. Impact: This study provides a description of the key, translational communication strategies that can be used by all health professionals to support healthcare interactions with people with Parkinson's.